Shock Hugoniot measurements of CH at Gbar pressures at the NIF. (March 2016) - Kritcher, A. L.; Doeppner, T.; Swift, D.; Hawreliak, J.; Nilsen, J.; Hammer, J.; Bachmann, B.; Collins, G.; Landen, O.; Keane, C.; Glenzer, S.; Rothman, S.; et al.
Abstract: Laboratory measurements of the shock Hugoniot at high pressure, exceeding several hundred Mbar, are of great importance in the understanding and accurate modeling of matter at extreme conditions. In this work we present a platform to measure the material properties, specifically the single shock Hugoniot and electron temperature, at extreme pressures of ∼Gbar at the National Ignition Facility (NIF). In these experiments we launch spherically convergent shocks into solid CH, using a Hohlraum radiation drive. X-ray radiography is applied to measure the shock speed and infer the mass density profile, enabling determining of the material pressure and Hugoniot equation of state. X-ray scattering is applied to measure the electron temperature through measurement of the electron velocity distribution.